2018
DOI: 10.17582/journal.jahp/2018/6.1.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parity, Period and Season of Calving on Production and Reproduction Traits on Deoni Cattle

Abstract: | A total of 710 lactation records of 274 Deoni cattle, maintained at ICAR-National Dairy Research Institute, Southern Campus, Bangalore were used to study the effect of non-genetic factors on production and reproduction traits. Lactation records of Deoni cows were classified into five parity (1, 2, 3, 4 and ≥5), six period of two years interval (2002 to 2013) and three seasons i.e., winter (November -February), summer (March -June) and rainy ( July -October). Statistical analysis was performed by using SPSS 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
7
6
1
Order By: Relevance
“…The interaction between breed and parity had a significant effect on the lactation period only (Table 1). These results in the current study agree with those of Toure et al (2019) in Mali, Basak and Das (2018) in India and Abera (2016) in Ethiopia.…”
Section: A-productive Traitssupporting
confidence: 94%
See 2 more Smart Citations
“…The interaction between breed and parity had a significant effect on the lactation period only (Table 1). These results in the current study agree with those of Toure et al (2019) in Mali, Basak and Das (2018) in India and Abera (2016) in Ethiopia.…”
Section: A-productive Traitssupporting
confidence: 94%
“…Similar results were also reported by Ayeneshet et al (2018) in local cows in Ethiopia and Sanad and Hassane (2019) in crossbred Friesian cattle in Egypt and they explained that the difference could be due to the number of cows used and the emergence of new generations during the period of calving. Meanwhile, no significant effect of year of calving on CI was reported by Basak and Das (2018) of Deoni cattle in India.…”
Section: -Calving Interval (Ci)mentioning
confidence: 88%
See 1 more Smart Citation
“…Effect of year of calving on TMY: Table (3) showed the effect of year of calving was significant on TMY. Similar agreement was observed by Basak and Das (2018) and Almasri (2010). Otherwise, Shafig et al (1992) reported the effect of year of calving on TMY was nonsignificant of crossbred cows (Friesian × Sahiwal) in Pakistan.…”
Section: A-productive Performance: 1-total Milk Yield (Tmy)supporting
confidence: 92%
“…Results showed increasing in the TMY with the progress of the parity and up to the fourth parity 1650 kg, then decreased after the Fourth parity (table 5), this could be increase capacity of feed intake compared to the cows of the first parity, and udder glands reached full development, while decreased TMY after the Fourth parity due to increased mortality of secret cells with age. as was also reported by others Al Masri (2010) and Basak and Das (2018). On contrary, Bahashwan (2020) concluded the effect of parity on TMY was nonsignificant.…”
Section: Effect Of Parity On Tmysupporting
confidence: 73%